A prototype to integrate a wireless sensor network with civil protection grid applications - Esteves, António (2009)
The present work was performed in the context of the CYCLOPS project, which aimed to exploit the Grid capabilities for Global Monitoring for Environment and Security (GMES) applications. The scenario exploited in the present work was the existence of remote wireless sensor networks, which could monitor and transmit real-time data from remote places, in order to prevent or react more accurately to situations of natural disasters. Considering a Wireless Sensor Network (WSN) as an instrument, we used the DORII middleware to integrate this instrument with gLite-based Grid computing and storage, allowing an effective and user friendly access to the instrument, as it is required by Civil Protection applications. The mentioned goal was achieved by (i) implementing an Instrument Element and several Instrument Managers, which virtualize the WSN; (ii) developing a Custom Java Interface to connect the Instrument Managers with sensors, performing the translation of the commands/data exchanged between them; (iii) implementing additional modules to permit a long duration (or offline) monitoring, saving the observed data in a database; (iv) implementing a Sensor Observation Service, following the OGC standards, providing the users with access to the database.